Processo de implantação da educação inclusiva no sistema Colégio Militar do Brasil: a influência dos elementos da cultura militar - Cardoso, Márcio dos Reis (2021)
The politics Brazilian education has increasingly emphasized the aspect of inclusion in recent years. This movement follows international trends and is in line with the regulations governing education in the country. The Military College System in Brazil has been looking for to adapt to this new reality. In this context, this study has aimed to understand the systematic implementation of Inclusive Education in this differentiated education network, from the perspective of culture. The research was carried out through a qualitative study, from document analysis and data collection. The population consisted of the target audience of Inclusive Education students regularly enrolled in the participating units, as well as the teaching agents involved in this process. In order to achieve the purpose of this investigation, a questionnaire was applied, aimed at the public participating. Data verification followed a qualitative approach, using the content analysis method. The primary results have focused on the identification of the main aspects related to the military culture that impact the inclusion process and the secondary results have focused on the characteristics of the model that has been adopted to implement this educational modality. The answers obtained indicate that the elements of the Brazilian military culture were absorbed on a large scale by The Military College System in Brazil and influence the implementation and consolidation of Inclusive Education in the System, some positively and others negatively, favoring this process and sometimes hindering this process.